Comparison of three therapeutic regimens for genotype‐3 hepatitis C virus infection in a large real‐life multicentre cohort. (3rd February 2020) - Soria, Alessandro; Fava, Marco; Bernasconi, Davide P.; Lapadula, Giuseppe; Colella, Elisa; Valsecchi, Maria G.; Migliorino, Guglielmo M.; D'Ambrosio, Roberta; Landonio, Simona; Schiavini, Monica; Spinetti, Angiola; Carriero, Canio; et al.
Abstract: Background & Aims: In the direct‐acting antiviral era, treatment of genotype‐3 HCV (HCV‐GT3) is still challenging. Real‐life comparisons between recommended regimens, sofosbuvir (SOF)+daclatasvir (DAC), SOF/velpatasvir (VEL), glecaprevir/pibrentasvir (GLE/PIB), are scarce. We aimed at filling this data gap. Methods: Sustained virological response 12 weeks after treatment completion (SVR12) was assessed for all HCV‐GT3 patients consecutively treated within the Lombardia web‐based Navigatore HCV‐Network; differences in SVR12 across regimens were evaluated by logistic regression. Results: Of the 2082 subjects with HCV‐GT3, 1544 were evaluable for comparisons between regimens: SOF + DAC (1023, 66.2%), SOF/VEL (369, 23.9%), GLE/PIB (152, 9.8%). Patients treated with former regimens were more frequently male, cirrhotic, HIV‐positive, pretreated, used ribavirin in their regimen, and had lower baseline HCV‐RNA. SVR12 was similar across groups: 94.8% in SOF + DAC, 97.6% in SOF/VEL, 96.7% in GLE/PIB ( P  = .065). At univariate analysis, SVR12 was associated with female gender (97.9% vs 94.8%, P  = .007) and lower median pretreatment Log10 HCV‐RNA (5.87 vs 6.20, P  = .001). At multivariate logistic regression analysis, treatment with SOF/VEL was associated with a higher likelihood of SVR12 than SOF + DAC, but only in the absence of ribavirin (98% vs 90.3%). Female gender and lower pretreatment HCV‐RNA were independently associated with SVR12. Conclusions: In a large real‐life setting of HCV‐GT3‐infected patients with a high proportion of cirrhosis, the success rate was remarkable. The slight advantage of SOF/VEL on SOF + DAC was significant only without ribavirin. The current prescription shift towards novel regimens (ie SOF/VEL and GLE/PIB) in easier‐to‐treat patients allows ribavirin‐free and shorter schedules without mining SVR12 in this <> genotype.